Worms mexicanske hieroglyffer. Om en kopi af et mixtekisk håndskrift i Det Kongelige Bibliotek - Nielsen, Jesper (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
NB: Artiklen er på dansk, kun resuméet er på engelsk. Jesper Nielsen: Worm’s Mexican hieroglyphs. About a copy of a Mixtec manuscript in The Royal Library. Among The Royal Library’s collection of manuscripts is a piece (NKS 2064 fol.) titled Hieroglyphica Mexicana quae in sui Recordationem Reliquit J. Ludolphus. The piece is a handwritten copy of a small part of the pre-Columbian Mixtec screen-fold book known as Codex Vindobonensis Mexicanus 1. Firstly, this article provides an account of the copy’s genesis and its historic value and research value, subsequently, it describes the historic and genealogic information contained in the copy. Hieroglyphica Mexicana is derived from Ole Worm’s (1588-1654) famous natural and cultural historical collection, but was originally exported by the German orientalist Hiob Ludolph (1624-1704) while visiting Duke William of Sachsen-Weimar-Eisenach in 1650, who had the codex in his cabinet. In 1651, Ludolph gave Ole Worm the copy while visiting Copenhagen. The copy is a drawing of the backside of Codex Vindobonensis, which tells about the Mixtec city of Tilantongos (Oaxaca, Mexico), three dynasties and covers the period from the 900s and up to the mid-1400s. The part which Ludolph chose to copy originated from the lower part of page XII of the codex and is about the second dynasty in the mid-1300s, including the marriage of ♀ 3 Rabbit, Spiderweb Stone and ♂ 9 House, Mexican Jaguar from the neighbouring state Teozacualco in the year 5 Reed (1355 A.D.) Ludolph’s original copy is far more precise than the print, which was published in Museum Wormanium, the catalogue on Worm’s collection, in 1655, and which has often been depicted when referring to Ludolph’s copy. In relation to our understanding of the original Codex Vindobonensis, it is possible that the copy shows details which have disappeared from the original since 1650.